(untitled) (International Journal of Biomedical and Advance Research, 2021)
Cancer is a sophisticated disease in which the proliferation of cells which are unrestrained lead to the development of tumour. A detailed research into the mechanisms underlying the development of tumour, has paved a way towards the characterization of tumour suppressors like miRNAs (microRNAs). miRNAs are considered to regulate the expression of more than 30 percentage of the entire gene in the cells of mammals. The miRNAs with the largest change in the levels of expression are not necessarily the ones that are most relevant. However, miRNAs which are expressed differentially have greater importance in a biological context in relation to the progression of cancer than miRNAs that target and modulate just a few transcripts of mRNA (messenger RNA). The application of miRNAs in the breast cancer therapeutics is an area of interest. In this paper, a new technique for analyzing this nature of modulation by miRNA, has been developed, which determines the binding regions of miRNAs to the mRNAs using a normalised correlation method. 30 breast cancer specific mRNAs and the various miRNAs that target each of the mRNAs, are considered for the analysis. The new correlation method identifies the binding regions of all the miRNAs with respect to the ground truth.